The Influence of ESG Scores on the Cost of Equity Capital in ASEAN-5: The Role of Country Governance and Tax Payments - Amrullah, Muhammad Faris; Siregar, Sylvia Veronica Nalurita Purnama (Jurnal Maksipreneur, 2025)
This study examines the impact of Environmental, Social, and Governance (ESG) scores on the cost of equity capital (COE) in ASEAN-5 countries, focusing on the moderating roles of national governance quality and tax compliance. Using panel data from publicly listed firms between 2018 and 2022, the study employs panel data regression analysis with both fixed and random effects models to capture cross-sectional and time-series variations. The results reveal three key findings: (1) higher ESG scores significantly lower the cost of equity, indicating that strong ESG performance reduces perceived risks and boosts investor confidence; (2) tax compliance has no statistically significant moderating effect on the ESG-COE relationship, possibly due to weaker institutional frameworks in the ASEAN-5 region; and (3) the reduction in the cost of equity is more pronounced in countries with strong national governance, emphasizing the role of institutional quality in enhancing the financial benefits of ESG practices. These findings highlight the importance of aligning corporate ESG strategies with strong governance systems to maximize financial and sustainability outcomes in the ASEAN region, offering valuable insights for investors, academics, and policymakers.